PEMANFAATAN DUOLINGO SEBAGAI INOVASI DIGITAL DALAM PEMBELAJARAN BAHASA INGGRIS DI SD ISLAM 06 KOTA PEKALONGAN - M. Dzakwan Makarim; Akhir Aulia; Nina Mir’atus Sa’adah; Marsha Aulia Salwa; Fatmawati Nur Hasanah (Qalam : Jurnal Ilmu Kependidikan, 2025)
This study investigates the use of Duolingo as a digital innovation to enhance English learning at SD Islam 06 Kota Pekalongan. Using a qualitative descriptive design, data were collected through observation, interviews, and documentation. The findings show that Duolingo increased students’ motivation, participation, and confidence through interactive gamified activities. It also improved vocabulary mastery and pronunciation while creating a more enjoyable learning environment. The application supports Technology-Enhanced Learning (TEL) and aligns with the Kurikulum Merdeka by fostering creativity, independence, and collaboration. Therefore, Duolingo is considered an effective tool for promoting engaging and meaningful English learning among elementary students.